Low system justification is associated with support for both progressive and reactionary social change - Liekefett, Luisa; Becker, Julia C. (European journal of social psychology, 2022)
Traditional definitions of political ideology state that right‐wingers support system stability, whereas left‐wingers support social change. However, during the last decade many right‐wing movements have been on the rise and demanded far‐reaching changes. We argue that both left‐, and right‐wing protestors reject the status quo, and are motivated to change it – albeit in opposing directions: either to increase equality (progressive social change), or inequality (reactionary social change). In two studies (NStudy1 = 453, NStudy2 = 614), both left‐, and right‐wingers scored lower on system justification than moderates. Further, latent profile analyses showed that supporters of progressive social change were characterized by low system justification and left‐wing ideology, whereas supporters of reactionary social change were characterized by low system justification and right‐wing ideology. This indicates that right‐wingers do not necessarily support system stability – instead, they reject the status quo and promote change in the direction of greater inequality.